2017
DOI: 10.1128/aem.01498-17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Peptidoglycan Hydrolase from Lytic Bacteriophages Atu_ph02 and Atu_ph03 Triggers Lysis of Agrobacterium tumefaciens

Abstract: To provide food security, innovative approaches to preventing plant disease are currently being explored. Here, we demonstrate that lytic bacteriophages and phage lysis proteins are effective at triggering lysis of the phytopathogen Agrobacterium tumefaciens. Phages Atu_ph02 and Atu_ph03 were isolated from wastewater and induced lysis of C58-derived strains of A. tumefaciens. The coinoculation of A. tumefaciens with phages on potato discs limited tumor formation. The genomes of Atu_ph02 and Atu_ph03 are nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 87 publications
0
29
1
Order By: Relevance
“…The potent bactericidal effect of phages is mainly attributed to their genome-encoded cell wall hydrolase, also called lysin, which exhibits a lethal effect by forming holes in the cell wall through peptidoglycan digestion (14). Evidence has shown that lysins exhibit a high level of antibacterial activity, and they have proven their effectiveness for the treatment of infections caused by bacteria resistant to conventional chemical antibiotics in diverse animal models (15)(16)(17). A number of studies have revealed the enormous potential of the use of phage lysins, which even surpasses that of intact phage, as therapeutics for MRSA infections (16,18).…”
mentioning
confidence: 99%
“…The potent bactericidal effect of phages is mainly attributed to their genome-encoded cell wall hydrolase, also called lysin, which exhibits a lethal effect by forming holes in the cell wall through peptidoglycan digestion (14). Evidence has shown that lysins exhibit a high level of antibacterial activity, and they have proven their effectiveness for the treatment of infections caused by bacteria resistant to conventional chemical antibiotics in diverse animal models (15)(16)(17). A number of studies have revealed the enormous potential of the use of phage lysins, which even surpasses that of intact phage, as therapeutics for MRSA infections (16,18).…”
mentioning
confidence: 99%
“…In addition, it has been shown that they can be useful against multiresistant bacterial strains [ 71 ]. Recent research proposed VAPGHs activity to treat plant diseases, such as those provoked by Agrobacterium tumefaciens [ 72 ]. Finally, to improve their bactericidal capacities, chimeric proteins can be created by combining several enzymes or by exchanging their functional domains.…”
Section: Potential Application Of Phagesmentioning
confidence: 99%
“…Attai et al [ 161 ] recently characterized an endolysin from bacteriophages Atu_ph02 and Atu_ph03 for the biocontrol of Agrobacterium tumefaciens. A. tumefaciens is a Gram-negative soil-borne bacterium that is the etiologic agent of crown gall disease in a variety of orchard and vineyard crops [ 162 ].…”
Section: Endolysins As Food and Environmental Decontaminantsmentioning
confidence: 99%
“…Its severity and widespread impact has contributed to it to becoming the subject of many recent studies [ 163 ]. The lytic protein displayed interesting properties, with the ability to not only rapidly lyse the cell, but to also block cell division, ensuring potent antimicrobial activity [ 161 ]. Therefore, the enzyme is a candidate for biocontrol of A. tumefaciens ; however, the method of implementation needs to be researched before a viable strategy for crop protection can be developed.…”
Section: Endolysins As Food and Environmental Decontaminantsmentioning
confidence: 99%